The Phenomenon of Convenience for Local Government Auditors Using Audit Techniques Conventional - Tantini, Dewi; Nuswantara, Dian Anita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Fraud cases continue to rise, particularly in the local government sector, demonstrating the continued weakness of auditors in detecting fraud. This situation raises the urgency of understanding how local auditors select and use fraud detection tools that best align with their competencies. This study uses a qualitative approach with a phenomenological method, where data is collected through semi-structured interviews with auditors who have direct experience in examining fraud cases. This study aims to explore the experience of regional auditors in choosing fraud detection tools. The study found that Excel is the most effective tool for finding indications of fraud, and direct evidence is the most effective approach to proving fraud. The findings in this study show that the selection of fraud detection tools is highly dependent on the competence of auditors. This study presents a qualitative approach with in-depth interviews to evaluate the effectiveness of regional auditor fraud detection tools, which have not been discussed much in previous studies. This study provides implications that policymakers and supervisory institutions can optimize auditor competency through training and integrating the use of conventional tools with modern audit technology.